Fracture toughness test of epoxy adhesive dissimilar joint with various adhesive thicknesses - Mohd Afendi, Rojan, Dr. (The Japan Society of Mechanical Engineers, 2014)
Link to publisher's homepage at https://www.jstage.jst.go.jp/